How to get banks to take less risk and disclose bad news - Harris, Milton; Raviv, Artur (Journal of Financial Intermediation, 2014)
There is wide agreement that before the recent financial crisis, financial institutions took excessive risk in their investment strategies. At the same time, regulators complained that banks did not reveal the extent of their difficulties in a timely fashion thus reducing the effectiveness of government intervention to prevent or mitigate the deleterious effects of the financial crisis. The purpose of this paper is to investigate how regulators can best use certain tools at their disposal to motivate banks to take less risk and to provide adverse information to regulators early. We argue that two tools, namely (i) allowing bank payouts to equity holders even when banks report they are in trouble and (ii) constraining banks’ future investment strategy when they are in trouble can achieve both goals. We show that, in some cases, it is optimal to use both of these tools in combination. That is, in such cases it is optimal to allow equity payouts when banks report they are in trouble, even though such payouts increase the incentive for banks to take excessive risk and even though these payments are financed by taxpayers. We also show that the more socially costly is constraining the bank’s portfolio selection or the more complex are the bank’s assets, the more likely it is that allowing larger payouts and fewer constraints is optimal. Finally we discuss how changes in bank capital requirements interact with inducing disclosure and preventing excessive risk taking.